2003
DOI: 10.1142/s0217979203023331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Binding Energy of Low Lying Excited States in a Quantum Well

Abstract: The temperature dependent binding energy of some low lying excited states for a compositional Quantum Well have been calculated for various impurity locations by extending the investigation of Elabsy.4 It has been observed that the temperature plays an important role in the binding energy of low lying excited states also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…We solved exactly the Schrödinger and Klein-Gordon equations for an electron under the pseudoharmonic interaction consisting of quantum dot potential and antidot potential in the presence of a uniform strong magnetic field − → B along the z axis and AB flux field created by an infinitely long selenoid inserted inside the pseudodot. We obtained bound state solutions including the energy spectrum formula (39) and wave function (44) for a Schrödinger electron. Overmore, for the Klein-Gordon electron, the positive energy equation (67) and wave function (68) is found for S conf ( − → r ) = +V conf ( − → r ) case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We solved exactly the Schrödinger and Klein-Gordon equations for an electron under the pseudoharmonic interaction consisting of quantum dot potential and antidot potential in the presence of a uniform strong magnetic field − → B along the z axis and AB flux field created by an infinitely long selenoid inserted inside the pseudodot. We obtained bound state solutions including the energy spectrum formula (39) and wave function (44) for a Schrödinger electron. Overmore, for the Klein-Gordon electron, the positive energy equation (67) and wave function (68) is found for S conf ( − → r ) = +V conf ( − → r ) case.…”
Section: Resultsmentioning
confidence: 99%
“…These two cases are reduced to the Schrödinger equation with a potential interaction V conf ( − → r ) and free field interaction solutions, respectively. Now we study the effect of the pseudoharmonic potential, the presence and absence of magnetic field B, the presence and absence of AB flux density ξ and the antidot potential on the energy levels (39). To see the dependence of the energy spectrum on the magnetic quantum number, m, we take the following values: magnetic field − → B = (6 T ) z, AB flux field ξ = 8, chemical potential V 0 = 0.68346 (meV ) and r 0 = 8.958 × 10 −6 cm [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nithiyananthi and Jayakumar [20] have studied the effect of temperature on the binding energy of low lying excited states in a quantum well and they found that the binding energy decreased with increase of temperature. Parascandalo et al [21] studied the effects of quantum confinement and electron-electron correlation in Si -deformed quantum wires.…”
Section: Introductionmentioning
confidence: 99%